KONSEP DASAR PENILAIAN DAN EVALUASI DALAM PEMBELAJARAN DI SEKOLAH DASAR - Hilda Sitriyana Mafea; Jeni T Dallo (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2026)
Assessment and evaluation are important elements in the learning process, providing valuable information for both teachers and students. This research aims to analyze and describe the basic concepts, objectives, functions, principles, assessment techniques, and evaluation steps in learning. The research uses a library research approach with descriptive analysis of relevant literature. The result of this study is that assessment and evaluation are essential elements in the learning process that aim to measure competency achievement, provide feedback, and improve learning quality. Diverse assessment techniques, ranging from written tests to project assessments, support a comprehensive eva luation of learners' cognitive, affective and psychomotor aspects. Principles such as validity, sustainability, fairness and objectivity should be used as guidelines to produce accurate and meaningful evaluations. In addition, systematic evaluation steps, from planning to data interpretation, help educators to develop more effective learning policies. This research confirms the importance of a deep understanding of the basic concepts of assessment and evaluation to support the achievement of optimal educational goals.